(untitled) (Bangladesh Journal of Agricultural Research, 2026)
Vermicompost is an important organic manure for maintaining soil fertility and sustainable crop production. Hence, the present study was conducted to evaluate the effectiveness of vermicompost (VC) with inorganic fertilizer on the yield and quality of cabbage (Brassica oleracea var. capitata) during two consecutive years of 2019-2021. There were five treatments: T1 = 100% RDF (N115P70K125S20Zn2 kg ha-1), T2 = 75% RDF + 4 t ha-1 vermicompost (VC), T3 = 100% RDF+ 3t ha-1 VC, T4 = 75% RDF + 3 t ha-1 VC and T5 = Control. The experiment was laid out in randomized complete block design with three replications. The highest cabbage head yield was found in T3 (100% RDF+ 3 t ha-1VC), which was 409% higher over the control. The maximum protein content (10.6%), vitamin- C (40.0 mg 100g-1) and firmness (1.93 kgf) were recorded in the same treatment. The treatment T3 also showed the highest gross margin while the maximum BCR (5.33), soil organic matter and total-N were recorded in T4. Therefore, 100% RDF + 3 t VC ha-1 can be recommended for quality cabbage production. Bangladesh J. Agril. Res. 47(4): 433-449, December 2022